Perancangan Training Kit Instalasi Perumahan Berbasis Internet of Things (IoT) - Gunawan, Fito; Islami, Syaiful; Sukardi, Sukardi; Candra, Oriza (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Internet of Things (IoT) technology is still very little used in the world of education today, for example the use of IoT in training devices, so it is highly recommended to be implemented and taught to the next generation through the application of Internet of Things (IoT) based training devices in schools or universities . To develop your capabilities, one way is to create an Internet of Things (IoT)-based housing installation training device that has been designed or supported by technology and can be controlled via smartphone. This research was carried out through several stages of production including software creation and design. such as using the Arduino IDE application which is used to create programming sketches on the Arduino nano board, in other words the Arduino IDE is used as a programming medium on the Arduino nano so that the Arduino nano can read measurement results from the Arduino nano board. PZEM-004T sensor and displaying it on an LCD (Liquid Crystal Display) as well as manufacturing and designing hardware as a framework component. Tool testing and measurements are carried out to analyze the performance of bardi components and ordinary components and to verify the suitability and performance of the training kit tools to be made. So that the tools made are of good quality and can be used according to their intended purpose. The test results show that the use of bardi components does not consume too much electrical power compared to ordinary components.